PERAN KONTEN MATERI PENDIDIKAN AGAMA ISLAM DI TIKTOK UNTUK MENINGKATKAN MINAT IBADAH SHOLAT BAGI SISWA DI MADRASAH TSANAWIYAH AN-NIZHAM TELANAIPURA KOTA JAMBI - Mechi Anesintia; Kasful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the rapid development of social media, particularly the TikTok application, which is widely used by teenagers, including madrasah students. Islamic Religious Education (PAI) content available on TikTok has the potential to become an alternative learning medium that can increase students' interest in performing worship, especially prayer. This study aims to determine the role of Islamic Religious Education content on TikTok in increasing students' interest in performing prayers at Madrasah Tsanawiyah An-Nizham Telanaipura, Jambi City. This study uses a descriptive qualitative approach. The research results show that the content of Islamic Religious Education material on TikTok plays a role in increasing students' interest in performing prayers. Content presented in a brief, engaging, and easily understandable manner can provide new insights into the importance of prayer and motivate students to be more disciplined in performing their worship. In addition, the use of social media as a means of conveying religious messages is considered closer to students' daily lives, making it easier to accept and understand. Thus, it can be concluded that the TikTok platform can be one of the supporting media in fostering awareness and interest in prayer among students.